L’anthropologie française au miroir de l’américanisme : politiques, savoirs, altérités - Elisabeth Cunin (Caravelle)
This article questions the transformations of Americanist anthropology and analyzes concrete examples situated in Mexico and Colombia. More than a reference to the French «founding fathers» of Americanism, it deals with differences and misunderstandings between Americanist and American anthropology. Beyond the oposition between an enchanted vision of the «discovery» of the New World and the charge corresponding to a colonialist proyect, the purpose is to examine through Americanism in practice, the links between anthropological study and political and scientific domination.